Impact of Quality Control on Risk Assessment of Internal Auditors of Selected Deposit Money Banks in Nigeria - Aliyu, Yusuf; Tijjani , Alh. Ali; Yusuf, Mohammed (Kashere Journal of Management Sciences, 2024)
After the successful implementation of risk assessment in internal audit unit of manufacturing sector, it is now being extensively applied in service sectors which include banks, to improve business performance. The purpose of this study is to examine of the impact of quality control on risk assessment of internal audit. The identification, assessment, and prioritization of risks followed by coordinated and economical application of the scarce resources to monitor, minimize, and control the impact and/or probability of unfortunate events is what is usually known as risk assessment. It introduces the idea that the likelihood of an event happening can be reduced, or its consequences minimized. If risk are not properly assessed and prioritized, time can be wasted in dealing with it. At the same time, spending too much time assessing and managing unlikely risks can divert resources that could be used more profitably. This study uses purposive sampling technique and judgmental method of sampling, primary data collection was used and one way ANOVA techniques was used in data analysis. The result of this study shows that, with Risk based approach to internal audit’s perspective on risk and audits changed, internal auditors have been offered an opportunity to create more value.